"From womb to tomb; we're bound to others": microbiome in forensic science - Beatrice Benedetti; Paola Roberti; Marta Ciuffi; Antonio Carai; Ernesto d'Aloja (Hygeia Press di Corridori Marinella, 2019)
Microbiome is a new field of interest in clinical medicine with high potential in forensic medicine. It could be used in several applications, such as post-mortem interval (PMI) estimation, personal identification, differential diagnosis of cause of death and toxicology. Regarding PMI, during the decomposition of a corpse, the passage of time involves changing in microbial population both outside and inside the corpse but also in surrounding soil (cadaver decomposition island). These variations could be hypothetically used as PMI indicators (microbial clock), even thanks to the development of machine learning approach. Another potential use of skin and saliva microbiome is personal identification thanks to its inter-individual variability and tendency to remain unvarying over time. It may also be helpful to link a person to a specific object that has been touched (microbial fingerprint). Furthermore, we could infer some information about health state of human subjects, comparing post-mortem and ante-mortem microbiome, but this field of research is quite new and needs further studies. Moreover, we have to consider the influence of microbiome metabolism in post-mortem toxicological evaluation; microbes could alter substances concentrations - for example of ethanol, gamma-hydroxybutyric acid (GHB) and nitrobenzodiazepines - due to enzymatic degradation and individual microbial metabolism. Finally, integration of microbiome and human being's transcriptomic analysis may be helpful to depict their complex interactions even after death.